Detection of δ Scuti Pulsators in the Eclipsing Binaries Observed by TESS - Chen, Xinghao; Ding, Xu; Cheng, Liantao; Zhang, Xiaobin; Li, Yan; Ji, Kaifan; Xiong, Jianping; Li, Xuzhi; Luo, Changqing (The Astrophysical journal. Supplement series, 2022)
Based on 2 minute cadence TESS data from sectors 1–50, we report the results of the systematic extraction of δ Scuti–type pulsations in the 6431 eclipsing binaries with orbital periods shorter than 13 days. A total number of 242 pulsators were found in those systems, including 143 new discoveries. We examined their pulsation properties based on the H-R diagram and the relationships between the dominant pulsation period P dom , orbital period P orb , and effective temperature T eff . As a consequence, 216 targets are likely δ Scuti stars (123 new), 11 likely γ Doradus– δ Scuti hybrid stars (8 new), 5 likely β Cephei stars (4 new), 4 likely δ Scuti– γ Doradus hybrid stars (3 new), 3 likely Maia stars (3 new), 2 likely pulsating red giants (1 new), and a new unclassified star. As for the six new δ Scuti pulsators in eclipsing binaries with P orb < 0.65 days, we found that three of them significantly exceed the upper limits of the P dom / P orb ratio. This may indicate that P dom and P orb are uncorrelated for them. Finally, we statistically analyzed the dominant pulsation periods of the 216 δ Scuti stars in eclipsing binaries. Those stars concentrate around 225 μ Hz and the proportion of stars in the high-frequency region is significantly higher than that of single stars, which could be ascribed to the mass-transfer process.